Ideal Amenability of Banach Algebras and Some Hereditary Properties - M. Eshaghi Gordji (Journal of Sciences, Islamic Republic of Iran)
Let A be a Banach algebra. A is called ideally amenable if for every closed ideal I of A, the first cohomology group of A with coefficients in I* is trivial. We investigate the closed ideals I for which H1 (A,I* )={0}, whenever A is weakly amenable or a biflat Banach algebra. Also we give some hereditary properties of ideal amenability.